2021
DOI: 10.1523/jneurosci.1303-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Contribution of Granular and Agranular Subdivisions of the Retrosplenial Cortex to Remote Contextual Fear Memory Retrieval

Abstract: The retrieval of recent and remote memories are thought to rely on distinct brain circuits and mechanisms. The retrosplenial cortex (RSC) is robustly activated during the retrieval of remotely acquired contextual fear memories (CFMs), but the contribution of particular subdivisions [granular (RSG) vs agranular retrosplenial area (RSA)] and the circuit mechanisms through which they interact to retrieve remote memories remain unexplored. In this study, using both anterograde and retrograde viral tracing approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 54 publications
(59 reference statements)
0
7
0
Order By: Relevance
“…We found that although the RSPag → PL projection was specifically active at recent recall (Figure 3I), its inhibition during this time did not affect memory retrieval (Figure 4J). Interestingly, it was recently reported that although the whole RSP is necessary for recent and remote recall, it is rather the granular subregion of the RSP and not the RSPag that is responsible for this effect, suggesting a dissociated role of the two RSP subregions which could explain our observations (Tsai et al, 2022). In contrast, INS → PL projection inhibition during recent recall resulted in decreased freezing (Figure 4K).…”
Section: Resultsmentioning
confidence: 48%
“…We found that although the RSPag → PL projection was specifically active at recent recall (Figure 3I), its inhibition during this time did not affect memory retrieval (Figure 4J). Interestingly, it was recently reported that although the whole RSP is necessary for recent and remote recall, it is rather the granular subregion of the RSP and not the RSPag that is responsible for this effect, suggesting a dissociated role of the two RSP subregions which could explain our observations (Tsai et al, 2022). In contrast, INS → PL projection inhibition during recent recall resulted in decreased freezing (Figure 4K).…”
Section: Resultsmentioning
confidence: 48%
“…Together, these findings emphasise the reliance of the three regions on each other, suggesting that together the subiculum and anterior thalamic nuclei facilitate information processing in the retrosplenial cortex, which is gated by its inputs from CA1 (Aggleton & O'Mara, 2022; Yamawaki, Corcoran, et al, 2019). In addition, a recent study found that some granular retrosplenial neurons in layer V project directly to CA1 of the dorsal hippocampus in mice (Tsai et al, 2022). These projections may help retrieve remotely acquired contextual fear memory, demonstrating a bidirectional interdependence between regions (Tsai et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a recent study found that some granular retrosplenial neurons in layer V project directly to CA1 of the dorsal hippocampus in mice (Tsai et al, 2022). These projections may help retrieve remotely acquired contextual fear memory, demonstrating a bidirectional interdependence between regions (Tsai et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Our results demonstrate a gRSC/dRSC specificity in cell type composition, as well as uncover differences between the gRSC and the neocortex (Figure 6). This may provide insight into clarifying functional differences between the gRSC and dRSC 10,[28][29][30][31] , as well as revealing differences in RSC information processing relative to the neocortex.…”
Section: Importance Of Understanding the Cell Types Of The Rscmentioning
confidence: 99%